Influence of Engine Speed and Injection Timings on In-Cylinder Heat Transfer for Port Injection Hydrogen Fueled Engine - M. M., Rahman; M. M., Noor; K., Kadirgama; R. A., Bakar (2010)
The overall heat transfer process within the in-cylinder for port injection hydrogen fueled internal combustion engine (H2ICE) has been investigated through simulation, while the experimental data has been utilized for validation purpose of the adopted numerical model. One-dimensional gas dynamics was used to describe the flow and heat transfer in the components of the engine model. The engine model is simulated with a variable injection timing, engine speed and equivalence ratio (φ ). Simulation has been executed for 60 deg ATDC ≤θ inj≤160 deg ATDC (during the intake stroke), 1000 ≤ rpm ≤6000 and 0.2 ≤φ≤1.2. The baseline engine model with gasoline fuel has been verified with experimental data and reasonable agreement has been achieved. The overall results show that there is a combined influence for the engine speed and equivalence ratio (φ ) on the overall heat transfer characteristics. The identification for the effect of the injection timing on the overall heat transfer characteristics has been failed because the injection issue is not considered within the combustion approach.